Adventure Racing: The Experiences of Participants in the Everglades Challenge. (January 2014) - Simpson, Duncan; Post, Phillip Guy; Tashman, Lauren Saenz
There has been little research devoted to understanding the sporting experience of Adventure Racing (AR) participants. Given the possible psychological benefits of AR participation, this investigation was undertaken to obtain additional insight into these competitors' experience of participating in the Everglades Challenge. Existential phenomenological interviews were conducted with 10 participants ranging in age from 34 to 64 years who took part in the 2011 Everglades Challenge. Qualitative analysis of the transcripts revealed a total of 498 meaning units that were further grouped into subthemes, majors themes, and a primary ground. A final thematic structure revealed Adventure as the primary ground for the four major themes of Pushing Limits, Community, Preparation, and Natural Elements. The results suggest that AR can be transformational in many ways and that it provides an avenue for exploring personal meaning and promoting psychological benefits.